Rapidly liver-clearable rare-earth core–shell nanoprobe for dual-modal breast cancer imaging in the second near-infrared window - Zhuxin Wei (BMC, 2021)
Abstract Background Fluorescence imaging as the beacon for optical navigation has wildly developed in preclinical studies due to its prominent advantages, including noninvasiveness and superior temporal resolution. However, the traditional optical methods based on ultraviolet (UV, 200–400 nm) and visible light (Vis, 400–650 nm) limited by their low penetration, signal-to-noise ratio, and high background auto-fluorescence interference. Therefore, the development of near-infrared-II (NIR-II 1000–1700 nm) nanoprobe attracted significant attentions toward in vivo imaging. Regrettably, most of the NIR-II fluorescence probes, especially for inorganic NPs, were hardly excreted from the reticuloendothelial system (RES), yielding the anonymous long-term circulatory safety issue. Results Here, we develop a facile strategy for the fabrication of Nd3+-doped rare-earth core–shell nanoparticles (Nd-RENPs), NaGdF4:5%Nd@NaLuF4, with strong emission in the NIR-II window. What’s more, the Nd-RENPs could be quickly eliminated from the hepatobiliary pathway, reducing the potential risk with the long-term retention in the RES. Further, the Nd-RENPs are successfully utilized for NIR-II in vivo imaging and magnetic resonance imaging (MRI) contrast agents, enabling the precise detection of breast cancer. Conclusions The rationally designed Nd-RENPs nanoprobes manifest rapid-clearance property revealing the potential application toward the noninvasive preoperative imaging of tumor lesions and real-time intra-operative supervision. Graphical abstract